Neuroactive Steroids: Receptor Interactions and Responses - Tuem, Kald Beshir; Atey, Tesfay Mehari (Frontiers in Neurology, 2017)
Neuroactive steroids are naturally occurring steroids, which are synthesized centrally as de novo from cholesterol and are classified as pregnane, androstane, and sulfated neurosteroids. Neuroactive steroids modulate many processes via interacting with gamma-aminobutyric acid (GABA), N-methyl-D-aspartate, serotonin, voltage-gated calcium channels, voltage-dependent anion channels, α-adrenoreceptors, X-receptors of the liver, transient receptor potential channels, microtubule-associated protein 2, neurotrophin nerve growth factor, and σ1 receptors. Among these, neurosteroids (especially allopregnanolone) have high potency and extensive GABA-A receptors and hence demonstrate anticonvulsant, anesthetic, central cytoprotectant and baroreflex inhibitory effects. Neurosteroids are also involved in mood and learning via serotonin and anti-nociceptive activity via T-type voltage-gated Ca2+ channels. Moreover, they are modulators of mitochondrial function, synaptic plasticity, or regulators of apoptosis, which have a role in neuroprotective via voltage- dependent anion channels receptors. For proper functioning, neuroactive steroids need to be in their normal level whereas excess and deficiency may lead to abnormalities. When they are below the normal, neurosteroids could have a part in development of depression, neuro-inflammation, multiple sclerosis, experimental autoimmune encephalitis (EAE), epilepsy, and schizophrenia. On the other hand, stress and attention deficit disorder could occur during excessive level. Overall, neuroactive steroids are very important molecules with major neuropsychiatric activity.